2021
DOI: 10.21315/tlsr2021.32.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A Consortium of Pseudomonas aeruginosa and Trichoderma harzianum for Improving Growth and Induced Biochemical Changes in Fusarium Wilt Infected Bananas

Abstract: Fusarium wilt of banana cannot be effectively controlled by current control strategies. The most virulent form that caused major losses in the banana production is Fusarium oxysporum f. sp. cubense Tropical Race 4 (Foc-TR4). Biocontrol of Foc-TR4 using microbial antagonists offers a sustainable and eco-friendly alternative. A consortium of biocontrol agents (BCAs), Pseudomonas aeruginosa DRB1 and Trichoderma harzianum CBF2 was formulated into pesta granules, talc powder, alginate beads and liquid bioformulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…In a similar study, a consortium of antagonistic bacterial strains consisting of Exiguobacterium indicum D1/8 and Bacillus cereus D1/17 were found to be effective in the control of the P. aphanidermatum damping-off of tomato compared to individual antagonists. Similarly, the combined application of Pseudomonas aeruginosa (bacterial biocontrol agent) and Trichoderma harzianum (fungal biocontrol agent) significantly reduced the severity of the Fusarium wilt of banana [ 59 ]. The compatibility between the antagonistic bacterial strains isolated from Moringa spp.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study, a consortium of antagonistic bacterial strains consisting of Exiguobacterium indicum D1/8 and Bacillus cereus D1/17 were found to be effective in the control of the P. aphanidermatum damping-off of tomato compared to individual antagonists. Similarly, the combined application of Pseudomonas aeruginosa (bacterial biocontrol agent) and Trichoderma harzianum (fungal biocontrol agent) significantly reduced the severity of the Fusarium wilt of banana [ 59 ]. The compatibility between the antagonistic bacterial strains isolated from Moringa spp.…”
Section: Discussionmentioning
confidence: 99%
“…When the banana seedlings were infected with FOC, proline accumulation levels significantly increased in the banana plant tissues. It was once thought to be an effective defense against oxidative stress and disease infection [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous study [ 21 , 22 ], instead of conventional fertilizer by alkaline fertilizer could significantly increase soil pH and then reduce the occurrence of banana wilt. Although some studies have also shown that biocontrol has an obvious effect on banana Fusarium wilt [ 10 , 23 , 24 , 25 ], the efficacy will be poor if soil acidity is not improved [ 21 , 22 ]. Biocontrol is one of the hot topics of banana Fusarium wilt control before release of the disease resistant variety.…”
Section: Introductionmentioning
confidence: 99%